2012
DOI: 10.1007/s10897-012-9517-7
|View full text |Cite
|
Sign up to set email alerts
|

22q11.2 Deletion Syndrome: Attitudes towards Disclosing the Risk of Psychiatric Illness

Abstract: Abstract22q11.2 Deletion Syndrome (22q11.2DS) is a common microdeletion syndrome with multisystem features. There is a strong association with psychiatric disorders. One in every four to five patients develop schizophrenia. Despite studies showing that early diagnosis and treatment are likely to lead to improved outcome, genetic counselors may be reluctant to discuss the risk of psychiatric illness. The aim of this research was to explore parental attitudes and genetic counselors' perspectives and practice reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 31 publications
4
54
0
2
Order By: Relevance
“…A common finding concerning the lack of empathy and knowledge around 22q11DS was reported amongst educators and health‐care professionals (Cohen et al, 2017; Goodwin & McCormack, 2017; Goodwin, McCormack, et al, 2017; Karas et al, 2014; Klingberg et al, 2010; Martin et al, 2012; Phillips et al, 2017), this exacerbated the frustration and left many parents feeling like they had to fight for the care and support that their child deserves (Cohen et al, 2017; Goodwin & Mccormack, 2017). As a result, many parents and caregivers expressed feeling hopeless and worried.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…A common finding concerning the lack of empathy and knowledge around 22q11DS was reported amongst educators and health‐care professionals (Cohen et al, 2017; Goodwin & McCormack, 2017; Goodwin, McCormack, et al, 2017; Karas et al, 2014; Klingberg et al, 2010; Martin et al, 2012; Phillips et al, 2017), this exacerbated the frustration and left many parents feeling like they had to fight for the care and support that their child deserves (Cohen et al, 2017; Goodwin & Mccormack, 2017). As a result, many parents and caregivers expressed feeling hopeless and worried.…”
Section: Resultsmentioning
confidence: 97%
“…Across the included studies, many parents reported feelings of powerlessness and frustration as a result of having to wait years for a diagnosis for their child (Bales et al, 2010a; Cohen et al, 2017; Costain et al, 2012), which resulted in increased uncertainty about the child's future (Bales et al, 2010a; Cohen et al, 2017; Costain et al, 2012; Goodwin & Mccormack, 2017; Goodwin, McCormack, et al, 2017; Karas et al, 2014; Martin et al, 2012). They also described a sense of relief when a diagnosis was given, and perceived that early justification for the child's symptoms can help psychological and clinical aspects of the illness earlier on in life (Cohen et al, 2017; Costain et al, 2012; Goodwin, McCormack, et al, 2017; Martin et al, 2012). Parents have praised the health care they received: one mother spoke about a pediatrician making the right referral in the process of finding a diagnosis (Bales et al, 2010a); another spoke about improved interactions between medical specialists and caregivers and patients when the clinicians were aware of the diagnosis (Costain et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations